Steps to evaluating a statewide internship program: Model, trainee, and student outcomes - Morrison, Julie Q.; Graden, Janet L.; Barnett, David W. (Psychology in the schools, 2009)
Internships play a pivotal role in the future of school psychology, and internship training is influenced by disciplinary trends including (a) an increased focus on accountability and demonstrating the positive impact of trainees' practices on student outcomes and (b) growing emphasis on scientifically based and empirically based practice. These influences also include greater sophistication in decision making as well as different ways of outcome‐focused decision making. System‐wide approaches such as Positive Behavior Support (PBS) and response to intervention (RTI) require high training demands to develop intervention‐related decision and accountability skills. Programmatically, accountability systems to meet the training needs of intervention services require scaling up. This article describes a multiyear developmental project bringing diverse universities together to institutionalize a statewide system of accountability. We share data from 3 years (N of interns = 278) and suggest recommendations for outcome‐oriented evaluation for other universities, agencies, school psychological services delivery units, or states. © 2009 Wiley Periodicals, Inc.